Whole-genome resequencing data reveal the genetic diversity of local chickens in southern Zhejiang and surrounding areas in China - Yawen Zhang; Bo Zhang; Ziwei Li; Fengxiang Hou; Yan Zhao; Junjie Jin; Bin Song; Wenjie Gu (Czech Journal of Animal Science)
China's local chicken breeds, especially those in the Zhejiang Province, are rich in genetic diversity owing to environmental heterogeneity and complex ecosystems. Distinctive local breeds have emerged through long-term natural selection and domestication. We investigated the genetic diversity and population structure of local chickens in southern Zhejiang and surrounding areas using whole-genome resequencing of 129 chickens from seven populations. A total of 1.8 terabytes of raw data was obtained, and 4 802 728 single nucleotide polymorphisms were detected. The Xianju chicken population exhibited the highest genetic diversity, while Yandang Partridge chickens were genetically distant from other chicken breeds. This study provides valuable information for conserving poultry genetic diversity and informs about breeding programmes of local Chinese chicken breeds.